2017
DOI: 10.1016/j.joca.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between weight loss in obese knee osteoarthritis patients and serum biomarkers of cartilage breakdown: secondary analyses of a randomised trial

Abstract: The clinical improvement after a substantial weight loss and weight maintenance in KOA patients was not associated with decrease in markers of cartilage breakdown Coll2-1 or Fib3-2, even with indications of a slightly negative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The decrease in these markers over the course of the study and two systemic markers of inflammation, MMP-derived inflammation (CRPM) and interleukin-6 (IL-6), were strongly associated with weight loss indicating that overweight and obese adults with KOA who lose weight experienced reduced inflammation at a systemic as well as tissue level 14 ( Table I). In contrast, among overweight KOA patients who followed a 16-week weight loss intervention and 52-week weight maintenance, the clinical improvement after weight loss and weight maintenance was not associated with change in serum markers of Coll2-1 and fibulin3-2 15 (Table I). Type II collagen is a major structural protein of the cartilage and together with other collagen types and non-collagenous proteins, such as COMP, provides a tensile meshwork for cartilage 2 .…”
Section: Association With Clinical Scores and Changesmentioning
confidence: 90%
“…The decrease in these markers over the course of the study and two systemic markers of inflammation, MMP-derived inflammation (CRPM) and interleukin-6 (IL-6), were strongly associated with weight loss indicating that overweight and obese adults with KOA who lose weight experienced reduced inflammation at a systemic as well as tissue level 14 ( Table I). In contrast, among overweight KOA patients who followed a 16-week weight loss intervention and 52-week weight maintenance, the clinical improvement after weight loss and weight maintenance was not associated with change in serum markers of Coll2-1 and fibulin3-2 15 (Table I). Type II collagen is a major structural protein of the cartilage and together with other collagen types and non-collagenous proteins, such as COMP, provides a tensile meshwork for cartilage 2 .…”
Section: Association With Clinical Scores and Changesmentioning
confidence: 90%
“…The current study examined the relationship of Pb-exposure with pain and discomfort in the musculoskeletal system and BTMs. As documented in the literature, cartilage break down 61 and lower cartilage thickness 62 are associated with knee osteoarthritis. The present study assessed the relationship between bone resorption markers and discomfort in the musculoskeletal system among workers.…”
Section: Discussionmentioning
confidence: 83%
“…Four studies investigated longterm urinary CTX-II response, of which three showed decreased levels and one showed no difference. A large study by Bartels et al 23 investigated another marker of collagen degradation, coll2-1, in an exercise cohort preceded by a weight loss intervention. Here, coll2-1 did not change significantly.…”
Section: Resultsmentioning
confidence: 99%